Comparison of Ligation of the Intersphincteric Fistula Tract and BioLIFT for the Treatment of Transsphincteric Anal Fistula: A Retrospective Analysis. Issue 3 (March 2020) - Zwiep, Terry M.; Gilbert, Richard; Boushey, Robin P.; Schmid, Sarah; Moloo, Husein; Raiche, Isabelle; Williams, Lara; Musselman, Reilly P.
Abstract : BACKGROUND: Ligation of the intersphincteric fistula tract is a sphincter-preserving technique for the treatment of anal fistulas. The BioLIFT modification involves the placement of a biologic mesh in the intersphincteric plane. Advocates of this modification state improved healing rates, however evidence for this is lacking, and this approach costs significantly more. OBJECTIVE: The purpose of this study was to compare the healing rates of the ligation of the intersphincteric fistula tract with the BioLIFT. DESIGN: This was a retrospective cohort study. SETTINGS: The study was conducted at a tertiary care hospital from April 2008 to April 2018. PATIENTS: All adult patients with transsphincteric anal fistulas were included. Patients were excluded if they had IBD, more than 1 fistula tract operated on simultaneously, or a previous attempt at repair. MAIN OUTCOME MEASURES: The primary outcome was primary healing of the fistula tract, and secondary outcomes included overall success, complications, and time to recurrence. RESULTS: There were 119 cases (75 ligation of the intersphincteric fistula tract and 44 BioLIFTs). One surgeon performed 84% of the BioLIFT cases. The primary healing rate was 75.0% versus 58.7% ( p = 0.08), and the complication rate was 22.7% versus 17.3% ( p = 0.48; BioLIFT vs ligation of intersphincteric fistula tract). After multivariate logistic regression, the BioLIFT had a significantly better healing rate (OR = 2.38 (95% CI, 1.01–5.62); p = 0.048). Median follow-up was 9 versus 29 weeks (BioLIFT vs ligation of intersphincteric fistula tract). Kaplan–Meier analysis demonstrated no difference in the time to recurrence ( p = 0.48). LIMITATIONS: This study was limited by the retrospective nature, different lengths of follow-up, and varying case numbers between the surgeons. CONCLUSIONS: The BioLIFT modification is safe and effective for the treatment of anal fistulas but has a higher cost. This modification warrants additional prospective studies to establish its benefits over the ligation of the intersphincteric fistula tract procedure. See Video Abstract at http://links.lww.com/DCR/B139 . COMPARACIÓN DE LIFT VERSUS BIOLIFT PARA EL TRATAMIENTO DE LA FÍSTULA ANAL TRANSFINTERÉRICA: UN ANÁLISIS RETROSPECTIVO: ANTECEDENTES: Ligadura del tracto de la fístula interesfintérica es una técnica para preservación del esfínter en el tratamiento de las fístulas anales. La modificación BioLIFT implica la colocación de una malla biológica en el plano interesfintérico. Protagonistas de la modificación mejoraron las tasas de curación, sin embargo, carecen evidencias definitivas y la técnica eleva costos significativamente. OBJETIVO: Comparar las tasas de curación de ligadura del tracto de la fístula interesfintérica con el BioLIFT. DISEÑO: Estudio de cohorte retrospectivo. AMBIENTE CLINICO: Hospital de atención de tercer nivel desde abril de 2008 hasta abril de 2018. PACIENTES: Se incluyeron todos los pacientes adultos con fístulas anales transfinteréricas. Los pacientes fueron excluidos si tenían enfermedad inflamatoria intestinal, más de un tracto fistuloso operado simultáneamente o con un intento previo de reparación. PRINCIPALES MEDIDAS DE VALORACION: El resultado principal fue la curación primaria del tracto fistuloso y los resultados secundarios incluyeron el éxito en general, las complicaciones y tiempo hasta recurrencia. RESULTADOS: Se registraron 119 casos (75 ligaduras del tracto de la fístula interesfintérica y 44 BioLIFT). Un cirujano realizó el 84% de los casos de BioLIFT. La tasa de curación primaria fue del 75.0% vs 58.7%, p = 0.08, y la tasa de complicaciones fue del 22.7% vs 17.3%, p = 0.48 comparando BioLIFT vs ligadura del tracto de la fístula interesfintérica. Después de la regresión logística multivariada, el BioLIFT tuvo una tasa de curación significativamente mejor (OR 2.38 [IC 95% 1.01-5.62], p = 0.048). La mediana de seguimiento fue de 9 vs 29 semanas (BioLIFT vs ligadura del tracto de la fístula interesfintérica). El análisis de Kaplan-Meier no demostró diferencias en el tiempo hasta la recurrencia (p = 0, 48). LIMITACIONES: Este estudio estuvo limitado por ser retrospectivo, las diferentes duraciones de seguimiento y el número variable de casos entre los cirujanos. CONCLUSIÓN: La modificación BioLIFT es segura y efectiva para el tratamiento de las fístulas anales pero tiene un costo más alto. Esta modificación amerita más estudios prospectivos para establecer los beneficios sobre ligadura del tracto de la fístula interesfintérica. Consulte Video Resumen en hhttp://links.lww.com/DCR/B139.